THE CONSEQUENCES OF GLOBALIZATION UPON SAFE TOURISM - Svetlana Mihić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Globalization, a phenomenon on the rise, is characterized by the free cross-bor- der movement of individuals, technologies, and capital. It has far- reaching consequen- ces for tourism, too, as it implies travel for leisure and business, and correspondingly, financial transfers between various nation states. Startinf from the status quo in the field, the current paper sets out to analyze the consequences and implications of globalization upon safe tourism and conduct a marketing research into the perceptions of consumers upon Serbia as a safe vacation destination for the purpose of safe tourism. Finally the research results will be presented and several solutions will be provided for improving security in tourism zones